2013
DOI: 10.1111/apa.12304
|View full text |Cite
|
Sign up to set email alerts
|

Why are there delays in seeking treatment for childhood diarrhoea in India?

Abstract: Improved care seeking for childhood diarrhoea in India is still constrained by access to a health facility and requires expansion and strengthening of the public health system. The caregivers, especially the mothers need to be educated about the importance of seeking timely treatment and the benefits of oral rehydration solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
22
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 17 publications
15
22
2
Order By: Relevance
“…Our findings revealed that caretakers were 1.8 times more likely to delay consulting a health facility if their child was a female than male. Similar findings were reported in studies done in Pakistan, India and Africa [16,18,19]. Surprisingly, age of child was not found to influence health facility consultation in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings revealed that caretakers were 1.8 times more likely to delay consulting a health facility if their child was a female than male. Similar findings were reported in studies done in Pakistan, India and Africa [16,18,19]. Surprisingly, age of child was not found to influence health facility consultation in this study.…”
Section: Discussionsupporting
confidence: 92%
“…These studies showed no differences in care-seeking behaviour or at times even a preference of the female sex (2426). Nevertheless, there is evidence supporting the assumption that girls experience higher treatment delays (2729) and are less likely to be examined by a qualified health care provider (30). Besides, the higher prevalence rates of diarrhoea in the first two years of life are analogous to previous findings (31).…”
Section: Discussionmentioning
confidence: 99%
“…The WHO predicts that there will still be about 5 million deaths in children younger than 5 years by 2025; most of these will be in developing countries, and most will be due to infectious diseases such as diarrhea (12). Diarrheal disease deaths are largely preventable if adequate treatment is sought early in the course of the illness (13). Recent studies suggest that rapid detection systems can decrease the costs associated with hospitalization and refine the application of antibiotic treatment (5).…”
Section: Discussionmentioning
confidence: 99%